Association Between SGLT2is and Cardiovascular and Respiratory Diseases: A Meta-Analysis of Large Trials - Yin, Dao-Gen; Qiu, Mei; Duan, Xue-Yan (Frontiers in Pharmacology, 2021)
The association between sodium-glucose cotransporter 2 inhibitors (SGLT2is) and various cardiovascular and respiratory diseases is unestablished. This meta-analysis aimed to explore whether use of SGLT2is is significantly associated with the occurrences of 80 types of cardiovascular diseases and 55 types of respiratory diseases. Large randomized trials of SGLT2is were included in analysis. Meta-analysis was conducted to synthesize risk ratio (RR) and 95% confidence interval (CI). Nine large trials were included in analysis. Compared to placebo, SGLT2is were associated with the reduced risks of 9 types of cardiovascular diseases (e.g., atrial fibrillation [RR 0.78, 95% CI 0.67-0.91], bradycardia [RR 0.60, 95% CI 0.40-0.89], and hypertensive emergency [RR 0.29, 95% CI 0.12-0.72]) and 11 types of respiratory diseases (e.g., chronic obstructive pulmonary disease [RR 0.77, 95% CI 0.61-0.97], asthma [RR 0.57, 95% CI 0.35-0.95], and sleep apnoea syndrome [RR 0.36, 95% CI 0.15-0.87]). The results of random-effects meta-analysis were similar with those of fixed-effects meta-analysis. No heterogeneity or only little heterogeneity was found in most meta-analyses. No publication bias was observed in most of the meta-analyses conducted in this study. SGLT2is were not significantly associated with the other 115 cardiovascular and respiratory diseases. SGLT2is are associated with the reduced risks of 9 types of cardiovascular diseases (e.g., atrial fibrillation, bradycardia, and hypertensive emergency) and 11 types of respiratory diseases (e.g., chronic obstructive pulmonary disease, asthma, and sleep apnoea syndrome). This proposes the potential of SGLT2is to be used for prevention of these cardiovascular and respiratory diseases.